FAKTOR-FAKTOR YANG BERPENGARUH PADA PENGUNGKAPAN INTELLECTUAL CAPITAL - Dwipayani, Anak Agung; Asri Dwija Putri, I.G.A. Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.11.TAHUN 2016, 2016)
The objective of this study is to find an empirical evidence about what factors are capable to influence the level of intellectual capital disclosure among Indonesian listed firms. The variables tested in this study are profitability ratio, leverage ratio, proportion of independent commisioner, ownership concentration, and quality of external audit. Intellectual capital disclosure are knowledge based disclosure and how this disclosure explains the way in which companies adapt their strategies in order to create and sustain competitive advantages. The population are taken from Indonesia Stock Exchange over the period 2010-2014 which are listed on LQ-45 Index. The sampling method on this study is purposive sampling method with total sample 225. The result shows that leverage ratio and quality of external audit are significantly influence intellectual capital disclosure.
Keywords: Profitability Ratio, Leverage Ratio, Proportion of Independent Commissioner, Ownership Concentration, Quality of External Audit, Intellectual Capital Disclosures